Iconic reading values in higher education students: identification and development of proposals - Esparza-Morales, Ivonne; Tarango, Javier; Machin-Mastromatteo, Juan D. (Revista General de Información y Documentación, 2017)
Iconic reading is understood as the appreciation of an image and its association with reality, through a process of recognition carried out by the recipient. The purpose of this article is to know if Mexican marketing students have the skills to develop reading comprehension competence based on the use of iconic text. A survey of basic, intermediate, and disciplinary competencies was applied to 72 students of this professional discipline at a public higher education institution in the state of Chihuahua, Mexico. It was found that they do not have the necessary visual literacy skills given their academic and disciplinary level. Therefore, an educational intervention design is proposed (functional in the curricular or extracurricular modality), with the intention of offering an option that allows students to acquire the competences required for their professional training.
Keywords: Iconic Reading; Information Literacy; Visual Literacy; University students; Marketing students; Mexican universities